Impact of a van der Waals interface on intrinsic and extrinsic defects in an MoSe2 monolayer. (15th August 2018) - Alvarez, Carlos J; Dau, Minh Tuan; Marty, Alain; Vergnaud, Celine; Le Poche, Helene; Pochet, Pascal; Jamet, Matthieu; Okuno, Hanako
Abstract: In this work, we study growth and migration of atomic defects in MoSe2 on graphene using multiple advanced transmission electron microscopy techniques to explore defect behavior in vdW heterostructures. A MoSe2 /graphene vdW heterostructure is prepared by a direct growth of both monolayers, thereby attaining an ideal vdW interface between the monolayers. We investigate the intrinsic defects (inversion domains and grain boundaries) in synthesized MoSe2, their evolution amid growth processing steps, and their influence on the formation and movement of extrinsic defects. Electron diffraction identifies a preferential interlayer orientation of 2° between MoSe2 and graphene, which is caused by the presence of intrinsic IBD defects. Extrinsic defects (point and line defects) are generated by in situ electron irradiation in the MoSe2 layer. Our results shed light on how to independently modify the MoSe2 atomic structure in vdW heterostructures for potential utilization in device processing.